2019
DOI: 10.1155/2019/8450947
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated T Cell Activation and Aberrant Cytokine Expression Profile in Systemic Lupus Erythematosus

Abstract: Accumulating evidence indicates a critical role for T cells and relevant cytokines in the pathogenesis of systemic lupus erythematosus (SLE). However, the specific contribution of T cells together with the related circulating cytokines in disease pathogenesis and organ involvement is still not clear. In the current study, we investigated relevant molecule expressions and cytokine levels in blood samples from 49 SLE patients and 22 healthy control subjects. The expression of HLA-DR and costimulatory molecules o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 30 publications
(32 reference statements)
0
28
0
Order By: Relevance
“…Its expression on T cells was proven to correlate with lupus activity either when analyzed on CD3 + T cells (47), CD4 + T cells (22, 4852), or CD8 + T cells (22, 49, 51, 52). It was shown that HLA-DR expression on CD3 + T cells was higher in lupus patients with anti-DNA antibodies as compared to HC (47) and was higher on CD8 + T cells in patients experiencing a lupus flare (22). Similar observations were made in patients with rheumatoid arthritis (21, 53), antiphospholipid syndrome (54) and with rejection in solid organ transplantation (55).…”
Section: Discussionmentioning
confidence: 99%
“…Its expression on T cells was proven to correlate with lupus activity either when analyzed on CD3 + T cells (47), CD4 + T cells (22, 4852), or CD8 + T cells (22, 49, 51, 52). It was shown that HLA-DR expression on CD3 + T cells was higher in lupus patients with anti-DNA antibodies as compared to HC (47) and was higher on CD8 + T cells in patients experiencing a lupus flare (22). Similar observations were made in patients with rheumatoid arthritis (21, 53), antiphospholipid syndrome (54) and with rejection in solid organ transplantation (55).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that IL-12 levels are increased in SLE patients (Uzrail et al, 2019[ 190 ]; Zhou et al, 2019[ 222 ]; Guimarães et al, 2017[ 72 ]) and that risk loci for IL12RB (You et al, 2015[ 215 ]) and genetic variants of IL12B (Paradowska-Gorycka et al, 2016[ 149 ]) are associated with SLE. On the other hand, however, it has been shown that there is a T H 17/T reg imbalance in patients with SLE (Talaat et al, 2015[ 179 ]) as well as a shift in the T H 1/T H 2 balance towards T H 2 cytokines (Uzrail et al, 2019[ 190 ]), suggesting that IL-12 is one cytokine among others in disease pathogenesis.…”
Section: Relevance Of Il-12 In Different Diseases and Disease Modelsmentioning
confidence: 99%
“…The principal underlying pathways involved in the pathogenesis are not fully understood but are believed to involve both the innate and adaptive immune response [ 10 ]. A loss of self-tolerance is widely believed to result in the formation of pathogenic autoreactive B and T-cells that in turn result in tissue damage [ 11 , 12 ]. The precise mechanism through which this occurs is not known, however, it is felt to involve a combination of genetic factors [ 13 ], environmental triggers [such as ultraviolet radiation and possible viral exposure] [ 14 ] and, given the marked female predominance of the disease, the influences of hormones [ 15 ].…”
Section: Introductionmentioning
confidence: 99%